2015
DOI: 10.1038/ncomms9440
|View full text |Cite|
|
Sign up to set email alerts
|

Structural diversity of supercoiled DNA

Abstract: By regulating access to the genetic code, DNA supercoiling strongly affects DNA metabolism. Despite its importance, however, much about supercoiled DNA (positively supercoiled DNA, in particular) remains unknown. Here we use electron cryo-tomography together with biochemical analyses to investigate structures of individual purified DNA minicircle topoisomers with defined degrees of supercoiling. Our results reveal that each topoisomer, negative or positive, adopts a unique and surprisingly wide distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
237
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(265 citation statements)
references
References 56 publications
26
237
1
1
Order By: Relevance
“…A number of studies have investigated the conformations of supercoiled plasmids using atomic force microscopy (20) or electron microscopy (19,25), which reveal conformations that are qualitatively in agreement with the configurations realized in our simulations.…”
Section: Comparison To Experimental Hydrodynamic Radius Measurementssupporting
confidence: 75%
See 3 more Smart Citations
“…A number of studies have investigated the conformations of supercoiled plasmids using atomic force microscopy (20) or electron microscopy (19,25), which reveal conformations that are qualitatively in agreement with the configurations realized in our simulations.…”
Section: Comparison To Experimental Hydrodynamic Radius Measurementssupporting
confidence: 75%
“…In addition, recent electron microscopy and molecular dynamics studies demonstrated that in very small DNA rings (336 bp), where DNA supercoiling requires the presence of sharply bent loops at the apices of the plectoneme, local denaturation may occur to accommodate kinks in the DNA (25). In this case, the short length of the DNA minicircles imposes a geometric constraint for writhing that likely enhances the formation of denatured regions that enable sharp bending.…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, the DNA in small circles has higher configurational entropy than in larger circles, which accommodate writhing by adopting a plectonemic form (Mitchell and Harris 2013). DNA supercoiling may thus affect the number of configurations adopted by the DNA (Irobalieva et al 2015), or the volume of the configurational space (Bednar et al 1994;Travers et al 2012). In other words, the repertoire of possible local structures will depend on the superhelical state of the DNA and the sign (either negative or positive) of coiling.…”
mentioning
confidence: 99%